The Effect of Microcylinder Shape on Enhancing the Aerodynamics of Airfoils at a Low Reynolds Number - Renata Gnatowska; Karolina Gajewska (Energies)
Passive flow control around airfoils, wind turbines, and submarines to enhance their aerodynamic properties is the subject of interest in several studies. Previous research provides different solutions, from basic changes in surface roughness and simple geometries to complex shapes and mechanical solutions. This article presents experimental research using the Particle Image Velocimetry (PIV) method on a NACA 0012 airfoil at a Reynolds number of 66,400. Initially, the airfoil was tested for three different angles of attack: 13°, 15°, 17°, and 19°. These tests revealed that angles of attack above 15° significantly increase boundary layer detachment, as shown in the normalized streamwise velocity fields <semantics>Ux</semantics>. In the second stage of the research, a different-shaped microcylinder with a characteristic dimension (d/c) of 0.01 was added to the leading edge of the airfoil at a high angle of attack of 17°. Unlike traditional vortex generators placed at the rear of the airfoil, this configuration aimed to reduce boundary layer detachment. The experiment demonstrated that the microcylinder effectively reduced boundary layer detachment at this angle of attack.